Thermally driven formation of polyphenolic carbonized nanogels with high anticoagulant activity from polysaccharides. (21st May 2021) - Mao, Ju-Yi; Unnikrishnan, Binesh; Chu, Han-Wei; Harroun, Scott G.; Chen, Yet-Ran; Wu, An-Tai; Chang, Huan-Tsung; Lin, Han-Jia; Huang, Chih-Ching
Abstract : Dry heating of sodium alginate to form graphene-like nanosheet-embedded carbonized nanogels. The nanogels with polyphenolic structures exhibit ultrastrong anticoagulant ability through the inhibition of various coagulation factors. Abstract : We have demonstrated that alginate with negligible anticoagulant activity can be converted into carbonized nanogels with potent anticoagulant activity through a solid-state heating process. The conversion of alginate into graphene-like nanosheet (GNS)-embedded polyphenolic-alginate nanogels (GNS/Alg-NGs) has been carried out through condensation and carbonization processes. The GNS/Alg-NGs exhibit much stronger anticoagulant activity (>520-fold) compared to untreated alginate, mainly because their polyphenolic structures have a high binding affinity [dissociation constant ( K d ) = 2.1 × 10 −10 M] toward thrombin. In addition, the thrombin clotting time delay caused by the GNS/Alg-NGs is 10-fold longer than that of natural polyphenolic compounds, such as quercetin, catechin, naringenin, caffeic acid, and ferulic acid. The thrombin- or kaolin-activated thromboelastography of whole-blood coagulation reveals that the GNS/Alg-NGs display a much stronger anticoagulant ability than that of untreated alginate and naturally sulfated polysaccharides (fucoidan). The GNS/Alg-NGs exhibit superior biocompatibility and anticoagulant activity, as observed with an in vivo rat model, revealing their potential as a blood thinner for the treatment of thrombotic disorders.